An introduction to tropical cash crops - McIlroy, Robert Joseph ([Ibadan] : Ibadan University Press, 1963)
The book is considered in details crops of commercial importance. Actual yields of crops are also reported. It is designed as an introductory textbook for students in the schools of Agriculture of tropical territories.
rpm 22/01/2019
loans
Keywords: Tropical crops; Cash crops